DESIGN OF MOTORCYCLE ENGINE COMPONENTS BASED ON FIXED SPECIFICATION - Samin, Mohd Shamam (Universiti Teknologi Petronas, 2004)
This Final Year Project report covers the findings of the author in his final year project which is to design the engine components of a motorcycle based on a specification obtained from existing motorcycle available in the market The main purpose of this project is to help the author inculcate the skills in applying the knowledge he has acquired in his science, engineering science, social studies and humanity courses. The object is not to teach new engineering courses but to guide the author on how to use purposefully and effectively what is already known to him. The project concerns primarily the system by which energy is converted into useful mechanical forms, and of mechanisms required to convert the output of the design to the desired forms. In order to do this, a proper step in design is important to avoid any mistakes. This not only related to the design of an engine component, but other design project. The precision of the design is taken into account where all the small and tedious things became important. In doing the project and progressing to the next step, some problem occurs and slowing the process. This is where project planning is important. The project begins by attaining the specification of the base model to be as a reference. Then the design stage commence whereby the dimensions of the components are calculated. Due to lack of information gathered, some of the parts to be design are revised and redesign according the specification needed. Finally, the drawings of the components were produced. This project is considered a success to the author as it meets the main objective of the project; to expose the author to the design procedure of engine components. It is recommended that for the future, the project be use to design a more powerful, fuel efficiency and cost saving engine.